Many-body interactions in photo-excited lead iodide perovskite - Trinh, M. Tuan; Wu, Xiaoxi; Niesner, Daniel; Zhu, X.-Y. (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Lead halide perovskite is emerging as a promising semiconductor material for thin film solar cells. Despite a large number of recent photophysical studies, the nature of photo-excitation in lead halide perovskite remains a subject of debate. Here we use transient absorption spectroscopy to re-examine lead halide perovskite thin films that have been reported to give very high solar cell efficiencies. We focus on many-body interactions that are manifested in (1) the transient Stark effect exerted by hot carriers on subsequent e–h pair generation; and (2) the Auger recombination due to three-body carrier–carrier interactions. These observations establish the dominance of free carriers from above band-gap excitation in lead halide perovskite. We also suggest the effective dynamic screening of charge carriers, likely due to orientational freedom of methylammonium cations in the perovskite lattice, and the presence of negligible charge carrier trapping in lead halide perovskite thin films grown in the presence of chloride precursors.